Kaji Eksperimen Sistem Organic Rankine Cycle Menggunakan Fluida Kerja R-134A Berkapasitas 1 KW - Adam Maulana Ibra; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Energy demand is increasing due to population growth and technological advances. Fossil energy of coal as fuel for Steam Power Plant (PLTU) is still widely used in various countries around the world because it provides human needs in large numbers. Coal burned in steam power plant produces a number of harmful pollutants such as NOx and SO3 which are the main causes of acid rain and particle pollution in the air. Organic Rankine Cycle (ORC) is technology to convert low temperature heat into the form of mechanical energy which can then be utilized to generate electrical energy without using fossil fuels. Heat exchangers used in ORC are evaporators and condensers. Refrigerant R134a used as working fluids. Experiments were performed to determine the performance of the ORC system with the temperature heat source of 95 ⁰C. Data collected in the form of temperature, pressure and volume flow rate. Experimental results obtained a maximum power of 279.58 Watt and maximum efficiency of 3.33 % at turbine inlet pressure 1.25 MPa and turbine inlet temperature of 67.76 ⁰C.Keywords: Organic Rankine Cycle, R134, Performance Analysis.